2001
DOI: 10.1063/1.1337587
|View full text |Cite
|
Sign up to set email alerts
|

Epitaxial growth of transparent p-type conducting CuGaO2 thin films on sapphire (001) substrates by pulsed laser deposition

Abstract: Transparent p-type conducting CuGaO2 thin films were prepared on α-Al2O3 (001) single-crystal substrates by pulsed laser deposition. The films were grown epitaxially on the substrates in an as-deposited state. X-ray pole figure analysis revealed that the films were composed of two types of epitaxial grains, both with c axes oriented perpendicular to the surface and a axes rotated 60° with respect to each other around the c axis. Observation of the CuGaO2 thin films by atomic force microscopy and high-resolutio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

17
274
1
3

Year Published

2010
2010
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 430 publications
(295 citation statements)
references
References 14 publications
17
274
1
3
Order By: Relevance
“…Generally, semiconducting behavior is observed for most p-type TCs such as delafossites (7,8,18), layered oxychalcogenides (12), and perovskite Sr-doped LaCrO 3 (19), which show thermally activated conductivity near room temperature and variablerange hopping at low temperatures due to the strong localization of carriers. In contrast, the transport properties of the p-type CuI thin films reported here are quite unusual, as can be seen from the temperature (T) dependence of the conductivity (σ) in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Generally, semiconducting behavior is observed for most p-type TCs such as delafossites (7,8,18), layered oxychalcogenides (12), and perovskite Sr-doped LaCrO 3 (19), which show thermally activated conductivity near room temperature and variablerange hopping at low temperatures due to the strong localization of carriers. In contrast, the transport properties of the p-type CuI thin films reported here are quite unusual, as can be seen from the temperature (T) dependence of the conductivity (σ) in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Further investigations found that other Cu-based delafossite oxides also possessed ptype TCO ability, e.g. CuInO 2 , CuGaO 2 and CuScO 2 which have optical gaps of 3.9 eV [13,14] 3.6 eV [15] and 3.3 eV [16] respectively.…”
Section: Introductionmentioning
confidence: 99%
“…5 Cu þ is linearly connected to two O 2À , resembling dumbbell shapes along the c axis. MO 6 Herein, the optical p-type TCO properties of CuBO 2 delafossite are investigated. CuBO 2 delafossite is prepared by solid state reaction, and characterized by X-ray diffraction (XRD), scanning electron microscopy (SEM), X-ray photoelectron spectroscopy (XPS), thermogravimetric and differential thermal gravimetric analyses (TGA, DTG), Seebeck coefficient (S), electrical conductivity, and ultraviolet-visible-near-infrared (UV-VIS-NIR), and fluorescence spectroscopies.…”
Section: Introductionmentioning
confidence: 99%